Multivariable run-to-run control of thermal atomic layer etching of aluminum oxide thin films - Yun, Sungil; Tom, Matthew; Ou, Feiyang; Orkoulas, Gerassimos; Christofides, Panagiotis D. (Chemical engineering research & design, 2022)
With the growing scarcity of semiconducting devices stemming from volatile prices, shortened supplies, and increased demand that are attributed to the Covid-19 pandemic, manufacturers are looking for efficient ways to facilitate the production of nanoscale semiconducting devices. Thermal atomic layer etching (ALE) is a promising method that can overcome the obstacles encountered during the production of semiconducting devices via conventional approaches by delivering precise dosages of reagent to etch monolayers of substrate surface material in a cyclic operation. However, thermal ALE has not been extensively studied and characterized to become fully embraced by the semiconductor manufacturing industry. Recent work by our group has led to the development of a multiscale computational fluid dynamics modeling framework that was used to optimally design a desirable reactor configuration and operating conditions for the thermal ALE process. Despite this progress, additional research is needed to ensure that the film quality is maintained in the presence of operational disturbances. Therefore, the present work is focused on the development of a multivariable run-to-run (R2R) control system to mitigate the impact of critical operational disturbances. It is demonstrated that the developed multivariable R2R control system can efficiently overcome the negative effects of unknown disturbances that may impact film uniformity by regulating input variables within a minimal number of batch runs. •Development of run-to-run control scheme for thermal atomic layer etching.•Multiscale computational fluid dynamics modeling of the process.•Controller tuning using process simulation data and implementation.•Evaluation of control scheme under practical disturbances.